(untitled) (Research, Society and Development, 2025)
This study aimed to evaluate bacteriophages isolated from a stream in Brazil that lyse Klebsiella spp. superbugs. Klebsiella pneumoniae is a Gram-negative bacterium associated with high infection rates worldwide and is currently listed by the World Health Organization (WHO) as a critical priority pathogen for the development of new antimicrobials. The indiscriminate use of antibiotics has accelerated the emergence of multidrug-resistant strains, underscoring the urgent need for alternative therapeutic strategies such as phage therapy. In this study, two bacteriophages (vB_MC_KP1 and vB_MC_KP2) were isolated from stream water in Minas Gerais, Brazil, a site receiving domestic sewage and used for irrigation and other human activities. Both phages specifically infected Klebsiella spp. and were characterized by in vitro assays assessing host range and physicochemical stability. They demonstrated high specificity, lytic activity against multiple Klebsiella species, and remarkable stability under a wide range of temperatures and pH values. These findings indicate that the isolated phages are environmentally persistent and hold potential for both therapeutic applications against multidrug-resistant K. pneumoniae and future use in environmental or food safety interventions. Further molecular characterization and in vivo studies are warranted to validate their application.